Computer Network Attacks and Modern International Law - A. L. Kozik (Vestnik MGIMO-Universiteta)
Computer network attacks (CNA) is a no doubt actual theoretical and practical topic today. Espionage, public and private computer-systems disruptions committed by states have been a real life. States execute CNA's involving its agents or hiring private hacker groups. However, the application of lex lata remains unclear in practice and still undeveloped in doctrine. Nevertheless the international obligations, which states have accepted under the UN Charter and other treaties as well as customs - with any related exemptions and reservations - are still in force and create a legal framework, which one cannot ignore. Taking into account the intensity level or the consequences of a CNA the later could be considered as an unfriendly, but legal doing, or, as a use of force (prohibited under the article 2(4) of the UN Charter), or - in the case the proper threshold is taken - as an armed attack (which gives the victim-state the right to use force in self-defence under the customs and the article 51 of the UN Charter). Researches in the field of lex lata applicability to the CNAs could highlight gaps and week points of the nowadays legal regime. The subject is on agenda in western doctrine, and it is a pity - not in Russian one - the number of publication here is still unsatisfied. The article formulates issues related to CNAs and the modern international legal regime. The author explores the definition, legal volume of the term CNA, highlights main issues, which have to be analyzed from the point of the contemporary law.